The effects of internal audit and board of directors on disclosure credibility in Jordan, and the moderating effects of corporate governance policies - Alqaraleh, Mithkal Hmoud Salem
Financial disclosures are potentially valuable sources of information for investors, but must be perceived as credible to be useful. Credible financial reporting enhances the efficient allocation of scarce financial capital to promising investment opportunities, which in tum maximizes the shareholders' wealth. Prior studies on Jordanian companies revealed considerable variations in the extent of disclosure by companies with regard to the quality, content and time lag in the reporting of financial statements. The incomplete and late information makes it difficult for the stakeholders and beneficiaries to take the right decision in relation to the firm. Some studies suggest that internal audit and board of directors, have the same impact on the credibility of the disclosure. Accordingly, this study examines the practices of internal audit and board of directors, and how these two factors impact the disclosure credibility in terms of completeness and timely of reporting by incorporating corporate governance policies as the moderating factor in the relationship. This study employs mix-method approach and used two types of data, primary and secondary data. Primary data on internal audit practices is collected through a survey on the CEO/CFO of Jordanian public listed companies while secondary data on board of directors' characteristics is gathered from the companies' annual reports. The final 172 questionnaires for companies are completed and usable were analysed by using multiple Regression and hierarchical Regression. The study finds positive significant relationship between internal audit practices (audit indep ndence, audit efficiency) and board of directors (board independence and CEO duality) with disclosure credibility in term of completeness. However, a negative ignificant relationship is found between incentives to auditors and board size with disclosure credibility (completeness). In addition, the study finds that internal audit (audit independence and audit efficiency) and board of directors (CEO duality) has a positive significant relationship with disclosure credibility in term of timeliness. However, there is no significant relationship between incentives to auditors and board independence with timely disclosure credibility. Corporate governance policies also act as a moderator in the relationship between CEO duality and disclosure credibility in term of completeness. The findings provide several implications for policymakers in terms of assessing corporate governance policies, particularly relating to board of directors, internal audi and disclosure in Jordanian public listed companies. The companies can enhance and improve the disclosure credibility in terms of completeness and timeliness according to the International Accounting Standards Board and corporate governance policies that have been established to reduce any negative impact on the disclosure credibility.